Foglar v nás: Záhada hlav a lomu - Jirásek, Ivo (Masaryk University Press, 2021)
Title in English: Foglar in us: the mystery of heads and quarries The presentation of the personality, work and influence of Jaroslav Foglar is not limited to a historical biographical sketch, but seeks, among other things, on the basis of an empirical survey (n = 1174), to provide a comprehensive professional treatment of a relatively complex social phenomenon. The evidence of the influence of the reading experience usually acquired in childhood on the whole future life, as well as the interest of several scientific disciplines (comic studies, literary science, religious studies, pedagogy) in the specific methods of the scout educator, writer of boys' literature and editor of several children's magazines is thus the first book venture going beyond theoretical considerations and hypotheses towards evidence based on surveys of readers and fans of Foglar's texts.